Effects of the Internet on Participation : Study of a Public Policy Referendum in Brazil - Spada, Paolo; Mellon, Jonathan; Peixoto, Tiago; Sjoberg, Fredrik M. (Taylor and Francis, 2016)
Does online voting mobilize citizens who otherwise would not participate? During the annual participatory budgeting vote in the southern state of Rio Grande do Sul in Brazil—the world's largest—Internet voters were asked whether they would have participated had there not been an online voting option (i-voting). The study documents an 8.2 percent increase in total turnout with the introduction of i-voting. In support of the mobilization hypothesis, unique survey data show that i-voting is mainly used by new participants rather than just for convenience by those who were already mobilized. The study also finds that age, gender, income, education, and social media usage are significant predictors of being online-only voters. However, technology appears more likely to engage people who are younger, male, of higher income and educational attainment, and more frequent social media users.